AN EMPIRICAL ANALYSIS OF RETAIL PURCHASE SATISFACTION TOWARDS DEVOTIONAL ANTIQUE CRAFT PRODUCTS - KUMAR S, Mr. AJITH (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analysethe satisfaction towards devotional antique craft products and estimate the retail purchase satisfaction among the devotees. The study was carried out among 400 respondents from eight prominent devotional places namely Tiruvannamalai, Tirutani, Palani, Madurai, Kanyakumari, Tiruchendur, Srirangam, and Tanjore. Highest satisfaction level was observed for the devotional antique craft product ‘god Idol’ and lowest satisfaction level was observed for the devotional antique craft product ‘tortoise on Plate’. Copper bangle, wall hanging, puja lamp, puja flower basket, god idol, goddess idol, aarti diya, copper ritual pot, prasadham bucket, religious bell, religious books and religious paintings are significant on the other hand frestol brass jyoti, silver plated pooja thali set, pooja rudrakshajapa mala, trident, tortoise on plate, vedic yajna set, brass vase, and small puja kalash are insignificant in the estimation of retail purchase satisfaction.